The Role of the Indonesian National Police in Realizing Restorative Justice in Cases of Criminal Defamation Through Social Media (Case Study at the Pematangsiantar Police Headquarters) - Zendrato, Ferawati; Ismaidar, Ismaidar; Firman Halawa (SEAN Institute, 2025)
The purpose of this study is to describe the role of the Pematangsiantar Police in realizing restorative justice in cases of criminal acts of defamation through social media and also to describe how defamation is regulated based on the perspective of Law No. 8 of 2011 as amended by Law No. 19 of 2016 concerning Information and Electronic Transactions contained in Article 27 paragraph (3) and the obstacles and efforts of the Pematangsiantar Police in realizing restorative justice. This research is descriptive and analytical in nature, obtained through normative and empirical legal approaches. Data collection techniques in this study were carried out using interview methods and literature studies. The types of data used in this study are primary data consisting of laws and secondary data consisting of various reading materials related to the research title, such as books, articles, journals, and literature. Based on the research results, it shows that (1) the regulation of criminal acts of defamation through social media has been regulated in Article 27 paragraph (3) of the ITE Law and the explanation of the implementation is in the Joint Decree of the ITE Law which is a guideline for the Pematangsiantar Police, (2) the role of the Pematangsiantar Police in realizing restorative justice in cases of criminal acts of defamation through social media includes receiving complaints, summonses, investigations and inquiries, examinations in which the police apply a resolution using the restorative justice method until it is successful with the stage of terminating the case if both parties agree to make peace, (3) The obstacles faced by the Pematangsiantar Police in realizing restorative justice at the investigation and inquiry stages are the difficulty in bringing the parties together, the failure to reach an agreement and the absence of a special budget allocated for the restorative justice process. To overcome these obstacles, efforts need to be made, namely: investigators should take a more humanistic approach to both parties, improve the quality and professionalism of human resources of law enforcement officers.